Implementation Of Genetic Algorithm In Advertising Scheduling On Commercial Radio Stations - siregar, idris; Zufria, Ilka; Nasution, Yusuf Ramadhan (Cattleya Darmaya Fortuna, 2023)
In this research, scheduling ad plays on a commercial radio station. Ad plays In this study, scheduling of advertisements was carried out on a commercial radio station. Ads are shown every day from Sunday to Saturday. There are two types of playing time, namely prime time and regular time. Prime time (pt) is 06-10 and 16:00-20:00, while regular time (rt) is 05-06, 11:00-15:00 and 21:00-24:00. The number of ad playback slots is 3 slots per hour and thus for pt time there are 15 slots, where at 16 to 20 hours there are 15 slots, so in total at pt time there are 30 slots per day and for rt time there are 15 slots and 21 hours -23 there are 3 clocks x 3 slots makes 9 slots. So in total at re time there are 27 slots. Prime time rules apply, namely the hours when the general public (listeners) have the greatest opportunity to listen to the radio, namely between 6:00-10:00 in the morning and 16:00-20:00 in the evening. The number of broadcasts of the same advertisement in one day is limited to prime time, which is 5 times, while for regular time it is 8 times. The radio scheduling process is carried out using a genetic algorithm which consists of the processes of chromosome initialization, selection, crossover and mutation. A chromosome represents the chromosomal matrix, namely Ad, Day and Time code. Each chromosome will be evaluated based on its fitness value which is calculated based on the number of penalties that occur on each chromosome in an individual. Where penalty 1 is the number of ad screenings more than once at a time while penalty 2 is the ad playing not at the specified type of time. The results of this study are to produce the best ad schedule by scheduling all ad data, the day and time of ad playing.